Remediation of Cr(VI) from wastewater using biochar of Indian Grass. Issue 1 (April 2021) - Karunakaran, S; Lineesh, P; Surendran, G; Baral, Saroj S; Kavitha, S; Jayakumar, C
Abstract: Chromium is extremely noxious unneeded for any living organism and its occurrence is unusual in nature. Many industrial activities such as mining, metal plating, wood preservation, dyes, pigments, tanning and textile industries makes pollution which cause major health hazards. The present study explores the possibilities using biochar from any carbonized material to use as source to remove the toxic material from any industrial effluent and particularly for Cr(VI). Batch process was accomplished to examine the outcome of various parameters to eliminate the Cr (VI) from the solutions. The rate of adsorption has been interrelated with all the parameters. The Cr(VI) adsorbed bio-char may be used as a fuel in Ferrochrome industry. From the study, it was experimental that adsorption kinetics obeys the pseudo second order kinetics. Experimental data follows the Langmuir isotherm. Intra-particle diffusion is most sluggish steps which determine the rate.